New insights into saline water evaporation from porous media: Complex interaction between evaporation rates, precipitation, and surface temperature. Issue 11 (3rd June 2017) - Shokri‐Kuehni, Salomé M. S.; Vetter, Thomas; Webb, Colin; Shokri, Nima
Abstract: Understanding salt transport and deposition patterns during evaporation from porous media is important in many engineering and hydrological processes such as soil salinization, ecosystem functioning, and land‐atmosphere interaction. As evaporation proceeds, salt concentration increases until it exceeds solubility limits, locally, and crystals precipitate. The interplay between transport processes, crystallization, and evaporation influences where crystallization occurs. During early stages, the precipitated salt creates an evolving porous structure affecting the evaporation kinetics. We conducted a comprehensive series of experiments to investigate how the salt concentration and precipitation influence evaporation dynamics. Our results illustrate the contribution of the evolving salt crust to the evaporative mass losses. High‐resolution thermal imaging enabled us to investigate the complex temperature dynamics at the surface of precipitated salt, providing further confirmation of salt crust contribution to the evaporation. We identify different phases of saline water evaporation from porous media with the corresponding dominant mechanisms in each phase and extend the physical understanding of such processes. Key Points: A conceptual evaporation curve is proposed to describe saline water evaporation from porous media Role of water evaporation through wet precipitated salt during evaporation has been illustrated Precipitated salt at surface induces rapid and complex surface temperature fluctuation at pore scale which influences evaporation dynamics